PENGARUH STRUKTUR UTANG, PERINGKAT KREDIT, DAN STRUKTUR MODAL TERHADAP IMBAL JASA AUDIT - Adi Darmawan Ervanto; Andry Irwanto (Jurnal Ekonomi dan Bisnis Airlangga, 2018)
Introduction: The purpose of this study is to empirically examine any effect of short-term debt structure, credit ratings, and capital structure on the audit fee. The sample used in this study are the companies listed in the PT Pemeringkat Efek Indonesia (Pefindo) and the Indonesia Stock Exchange. Methods: Data were analyzed using linear regression.The independent variables in this study are the proportion of short-term debt, credit ratings, and capital structure. Dependent variable is audit fee. This research uses the control variables representing firm size, its complexity, and risk. Number of assets and current assets to total assets ratio represent the size of the company. Number of business segments and the proportion of export sales to total sales represent the complexity of the company. Risk represented by the ratio of short-term liabilities to total assets, short-term liabilities to total assets ratio, quick ratio, and return on assets. Results: Hypothesis testing shows that the proportion of short-term debt does not significantly influence audit fee. Ratings have a negative impact on the audit fees of listed companies in Indonesia's credit rating. Capital structure does not significantly influence audit fee. Conclusion and suggestion: This study has limitations that are audit fee is measured by the natural logarithm of the nominal value of professional fees expense presented in the financial statements of the company and there is a possibility of mediating variables such as risk governance and audit, in examining impact of the proportion of debt and capital structure on audit fee.